Metabolomics profiling to characterize cerebral ischemia-reperfusion injury in mice - Chen, Qiong; Zhou, Ting; Yuan, Jun-jie; Xiong, Xiao-yi; Liu, Xue-hui; Qiu, Zong-ming; Hu, Lin-lin; Lu, Hui; He, Qian; Liu, Chang; Yang, Qing-wu (Frontiers in Pharmacology, 2023)
Cerebral ischemia, resulting from compromised blood flow, is one of the leading causes of death worldwide with limited therapeutic options. Potential deleterious injuries resulting from reperfusion therapies remain a clinical challenge for physicians. This study aimed to explore the metabolomic alterations during ischemia-reperfusion injury by employing metabolomic analysis coupled with gas chromatography time-of-flight mass spectrometry (GC-TOF-MS) and ultraperformance liquid chromatography quadrupole (UPLC/Q)-TOF-MS. Metabolomic data from mice subjected to middle cerebral artery occlusion (MCAO) followed by reperfusion (MCAO/R) were compared to those of the sham and MCAO groups. A total of 82 simultaneously differentially expressed metabolites were identified among each group. The top three major classifications of these differentially expressed metabolites were organic acids, lipids, and organooxygen compounds. Metabolomics pathway analysis was conducted to identify the underlying pathways implicated in MCAO/R. Based on impactor scores, the most significant pathways involved in the response to the reperfusion after cerebral ischemia were glycerophospholipid metabolism, linoleic acid metabolism, pyrimidine metabolism, and galactose metabolism. 17 of those 82 metabolites were greatly elevated in the MCAO/Reperfusion group, when compared to those in the sham and MCAO groups. Among those metabolites, glucose-6-phosphate 1, fructose-6-phosphate, cellobiose 2, o-phosphonothreonine 1, and salicin were the top five elevated metabolites in MCAO/R group, compared with the MCAO group. Glycolysis, the pentose phosphate pathway, starch and sucrose metabolism, and fructose and mannose degradation were the top four ranked pathways according to metabolites set enrichment analysis (MSEA). The present study not only advances our understanding of metabolomic changes among animals in the sham and cerebral ischemia groups with or without reperfusion via metabolomic profiling, but also paves the way to explore potential molecular mechanisms underlying metabolic alteration induced by cerebral ischemia-reperfusion.